Digestive System Recent Advances - Qi, Xingshun; Koruth, Sam (IntechOpen, 2020)
The book focuses on the recent advances in the digestive system. It is composed of 3 sections: gastrointestinal duct, liver, and biliary system. There are 9 chapters: peptic ulcers; mid-gastrointestinal bleeding; gastrointestinal manifestations of IgA vasculitis; biomechanics of intestinal contractions; evaluation of serum sodium change after terlipressin in cirrhosis; history and background of biliary system; gallbladder carcinoma; ERCP for cholecysto-choledocholithiasis; and cystic artery variations and associated vascular complications in laparoscopic cholecystectomy. The knowledge presented in this book should be valuable for family physicians, internists, gastroenterologists, hepatologists, endoscopists, radiologists, and pathologists who are interested in digestive diseases to guide the clinical practice and management. This book should be also useful for patients and their relatives to better understand the digestive system.